Designing English Syllabus for Islamic Education Study Program at IAIN Palopo - Sagita, Reski Jayanti; Sahraini, Sahraini; Syam, Andi Tenrisanna (FOSTER: Journal of English Language Teaching, 2020)
This research aimed to design the English syllabus for first semester students of the Islamic Education Study Program at IAIN Palopo. Based on the observation in June 2019, the researcher found several problems from the previous syllabus, such as the syllabus used general English, not specific English; the syllabus served a little portion of the discussion on topics of students’ needs and interests of Islamic Education. The research design used in this research was Research and Development (R&D) utilized the 4D model. It consists of defining, designing, developing, and disseminating. The procedures included analyzing English materials needed by the students of the Islamic Education study program then design the syllabus. The designed English syllabus for students of the Islamic Education study program at IAIN Palopo includes learning goals, learning material, learning methodology, learning indicators, and learning media. The product was tried out to the second semester of students of the Islamic Education study program at IAIN Palopo. The instruments were used in this research were questionnaires for need analysis and observation sheets for three expert validators and students’ perception. In this research, three experts were involved in order to validate the product. There were five systematic aspects that they validate of the product: Format Syllabus, Syllabus Content, Language and Writing, and Time allocation. Therefore, the result indicated that based on the experts’ validation as well as try-out design result, the product of this research was appropriate to be applied for students of the Islamic study program in the first semester as the primary syllabus for the English course.